CHARACTERISTIC OF LEMPOK QUALITY IN BENGKULU CITY - Arsat Koto; Evanila Silvia; Kurnia Herlina Dewi (Jurnal Agroindustri, 2015)
The aim of this study was to identify the quality characteristics of durian lempok in Bengkulu City and compare the quality characteristics lempok with SNI 01-4313-1996. The sample of lempok were taken from 2 home industries that the largest producer in Bengkulu City. The study was conducted three phases: 1) survey and interviews to determine the home industry with the largest production capacity in Bengkulu City, 2) random sampling in production at 3 times production; and 3) analysis of samples in terms of water content, the content of artificial sweeteners, TPC, texture, and pH. Data were analyzed descriptively. The results showed that the water content lempok durian on home industry A is 23% and B is 27%; artificial sweetener content between lempok is 0; TPC lempok is 63 x 105 colonies/g (A) and 116 x 105 colonies/g (B); lempok texture is 9.122 cm/10 g/10 s (A) and 8.955 cm/10 g/10 s (B) and pH of lempok 5.6 (A) and 5.4 (B). So the quality of durian in Bengkulu City lempok that achieve SNI No. 01-4313-1996 is an artificial sweetener content while the rest (moisture and TPC) does not achieve the standards.